Actualisation of the vestimentary code in the context of the soviet fashion discourse of the 1960s (axiological aspect) - L. Yu. Manasyan; T. M. Grushevskaya (Гуманитарные и юридические исследования)
The article characterises the Soviet fashion discourse of the 1960s with a special emphasis on the value system of the period under analysis. Fashion is considered and analysed as one of the semiotic systems. The concept of “the vestimentary code” (R. Barthes’s term) is studied, which is preceded by an analysis of the concept of “fashion” in the context of various types of cultural semiotics that make up the interdisciplinary field of research. The present work is based on the definitions of the concept of “fashion” given in various dictionaries, characterising its understanding as an interdisciplinary phenomenon in such fields as philosophy, aesthetics, ethics, cultural studies, sociology, psychology, linguistics. It is shown that the ambiguous attitude to this concept is due to its multidimensional nature; fashion covers many areas of human activity, so that both everyday and scientific views on this phenomenon are formed. As a phenomenon of everyday life, fashion is understandable to every individual, and from the point of view of the theoretical representation of its status, fashion symbolises the totality of sociocultural and historical processes, acting as one of the culture codes. The scientific novelty of the proposed study lies in the fact that the problem of the Soviet fashion discourse of the 1960s is for the first time considered as a linguistic problem. The fashion of the analysed period is characterised, on the one hand, by its revolutionary nature, expressed in its various directions (including in the styles of youth subcultures – mods, rockers, skinheads, hippies), and, on the other hand, by the specificity of its adaptation in our country, taking into account the sociocultural and the ideological contexts. The relevance of the topic under study from the point of view of discursive realisation arises from the need to determine by what means the features of the vestimentary code are represented in the context of the Soviet official fashion discourse of the 1960s. It is revealed that the specificity of the vestimentary code has a clear value benchmark that characterises this discourse unfolding on the pages of the Soviet media. The conclusion is made about the importance of the verbal component of the vestimentary code in the fashion discourse of the analysed era in our country.